Type IIA Secreted Phospholipase A2 in Host Defense against Bacterial Infections. Issue 4 (April 2020) - van Hensbergen, Vincent P.; Wu, Yongzheng; van Sorge, Nina M.; Touqui, Lhousseine
Abstract : The enzyme type IIA secreted phospholipase A2 (sPLA2-IIA) is crucial for mammalian innate host defense against bacterial pathogens. Most studies have investigated the role of sPLA2-IIA in systemic bacterial infections, identifying molecular pathways of bacterial resistance against sPLA2-IIA-mediated killing, and providing insight into sPLA2-IIA mechanisms of action. Sensitization of (antibiotic-resistant) bacteria to sPLA2-IIA action by blocking bacterial resistance or by applying sPLA2-IIA to treat bacterial infections might represent a therapeutic option in the future. Because sPLA2-IIA is highly expressed at mucosal barriers, we also discuss how sPLA2-IIA is likely to be an important driver of microbiome composition; we anticipate that future research in this area may bring new insights into the role of sPLA2-IIA in health and disease. Highlights: sPLA2-IIA is an endogenous antimicrobial protein produced by many tissues and host cells, and displays high constitutive expression at barrier sites and inducible expression in the circulation. sPLA2-IIA is unique in its particular selectivity and potency in killing Gram-positive bacteria; it plays an underappreciated role in defense against Gram-negative pathogens. Bacteria can interfere with sPLA2-IIA-mediated killing through manipulation of its expression or through cell-envelope modifications and effective repair mechanisms. On mucosal surfaces, sPLA2-IIA expression impacts on the composition of the microbiome. sPLA2-IIA could be used as a stand-alone therapeutic agent, or as an adjunct therapy to existing antibiotics, to treat infections caused by antibiotic-resistant bacteria.